Population size and nesting peculiarities of the black-headed gull Chroicocephalus ridibundus (Linnaeus, 1766) on the territory of water treatment facilities - Mamedova, Yulia; Chaplygina, Angela (Bìologìčnì studìï, 2024)
Background. Today, the black-headed gull inhabits man-made areas of wastewater treatment facilities (WTF) to comensate for the the reduction of natural aquatic and wetland habitats. Over the last decade, a nearly tenfold increase in its population has been recorded, despite a low reproduction rate. This fact indicates the lack of stability in the bird population, necessitating thorough research. Materials and Methods. The analysis of the population size and biological characteristics of black-headed gulls involved censuses and observations at the WTF of the city of Kharkiv using conventional methods during the spring-summer periods of 2020–2021 and 2023. Results. The population of the black-headed gull reached its peak in the third decade of May 2020 (2637 individuals) and 2023 (2124 individuals), as well as in the second decade of May 2021 (3949 individuals). The maximum nesting density was observed on sludge sites (SS) of wastewater treatment facilities that are most similar to natural habitats, where dried mud alternates with water patches and vegetation at the bottom and around the perimeter (Type V): 236.7±26.7 pairs/ha in 2020 and 242.9±28.5 pairs/ha in 2021. The majority of nests were found in the first decade of May 2021 and the third decade of May 2020. The black-headed gull forms mixed-species, occasionally monospecific subcolonies. Nesting in association with it were: Sterna hirundo, Anas platyrhynchos, Spatula clypeata, Vanellus vanellus, Charadrius dubius, Himantopus himantopus, Fulica atra, Gallinula chloropus, and Aythya ferina. The size of the complete black-headed gull clutch was 3.1±0.4 eggs (n = 190). The egg dimensions were 50.9±2.1 ´ 36.2±1.1, with a mass of 34.6±2.8 g. Regarding shell coloration, five types of background colors were identified. Mass egg laying occurred from the third decade of April to the first decade of May, constituting 40.3 % (n = 993) in 2020 and 62.3 % (n = 1757) in 2021. The egg-laying period extended from April to July, with the latest non-incubated clutches recorded in the first decade of July (3.07.2020). The first chicks were found in nests in the first decade of May, while mass hatching occurred in the second half of May. The latest registration dates of the birds on nesting territories were in the second decade of July for 2020 and 2023, and the first decade of August for 2022. The nesting season duration varied from 125 to 140 days in different years. Autumn migration commenced with summer relocations and concluded from late October to early November. The reproductive success – the percentage of nestlings that fledged and successfully achieved flight – constituted 29.2 % (n = 2404 of laid eggs) in 2020, and 15.5 % (n = 6138) in 2021. The majority of offspring perished due to changes in water levels (prolonged rainfall or industrial wastewater discharge), predation, disturbance factors, etc. Conclusion. The colonial nesting of the black-headed gull creates favorable conditions for the habitation and reproduction of various bird species, including rare ones, which is essential for their conservation.